Pengaruh Media Sosial, Citra Merek, dan Persepsi Harga Terhadap Keputusan Pembelian Pada Produk Eiger Adventure - Sandy Eko Prakoso; Rully Arifiansyah (J-CEKI : Jurnal Cendekia Ilmiah, 2023)
This research aims to evaluate the influence of social media, brand image, and price perception on purchasing decisions regarding Eiger Adventure products. The method used in this study is quantitative, involving the collection of numerical data and statistical analysis. The research population consists of consumers of Eiger Adventure. The sample size studied is 100 respondents, selected using accidental sampling. The collected data is then analyzed using multiple linear regression analysis because there are more than one independen variables that are being evaluated. The results of this study conclude that social media, brand image, and price perception have both partial and simultaneous influence on purchasing decisions regarding Eiger Adventure products.